iSpring Suite Multimedia to Improve Akidah Akhlak Learning Outcomes: Multimedia iSpring Suite untuk Meningkatkan Hasil Belajar Akidah Akhlak - Khairunnisa, Khairunnisa; Azhari, Muhammad (Indonesian Journal of Innovation Studies, 2025)
General Background: In the digital age, reliance on conventional learning methods may hinder educational progress and student outcomes. Specific Background: At MTs Swasta Swadaya Batang Serangan, the Akidah Akhlak subject suffers from low student engagement and suboptimal learning results due to passive instructional methods. Knowledge Gap: While various studies have addressed multimedia learning, few have specifically evaluated the application of iSpring Suite in religious education contexts at the junior high school level. Aims: This study aims to examine the impact of multimedia-based learning using the iSpring Suite application on student learning outcomes in Akidah Akhlak. Results: Employing a quasi-experimental design with 64 eighth-grade students, findings reveal significant differences between experimental and control groups: the experimental group improved from a mean pretest score of 53.72 to a posttest score of 70.88, while the control group improved from 48.72 to 56.78. The t-test result (t = 3.947, p < 0.05) confirms the statistical significance. Novelty: Unlike prior studies, this research integrates iSpring Suite in a religious education subject using an experimental approach rather than development-based research. Implications: The findings underscore the importance of integrating engaging digital tools in religious studies to foster improved understanding and learner performance, offering guidance for educators in adopting effective multimedia strategies.Highlight : iSpring Suite-based multimedia significantly improves students’ learning outcomes in Akidah Akhlak. Interactive multimedia helps clarify abstract concepts through engaging content. Teachers play a vital role in integrating digital tools to enhance learning effectiveness. Keywords : Learning Multimedia, iSpring Suite, Learning Outcomes, Akidah Akhlak, Grade VIII Students